What is habitat sensitivity? A quantitative definition relating resistance, resilience, and recoverability to environmental impacts - Cody J. Dey; Erik I. Tuononen; Emma E. Hodgson; D. Andrew R. Drake; Marten A. Koops; Cindy Chu (Canadian Science Publishing, 2024)
Habitat sensitivity is a consideration for decision-making under environmental laws in many jurisdictions. However, habitat sensitivity has been variously defined and there is no consistent approach to its quantification, which limits our understanding of how habitat sensitivity varies among systems and in response to different pressures. We review various definitions offered in the scientific literature and policy documents before suggesting a universal framework for habitat sensitivity as (i) a habitat trait that defines the ecological impacts from a given pressure, (ii) which is composed of three components (habitat resistance, resilience, and recoverability), and (iii) which is quantified by measuring the change and recovery in the state of key habitat attributes in response to pressures. In addition, we provide guidance toward a consistent approach to assessing habitat sensitivity, which includes the use of pressure benchmarks and standardized metrics of change in key habitat attributes to create a common scale for comparison among habitat attributes and pressures. Our framework and recommendations should help to standardize the way in which habitat sensitivity is defined and assessed, and could be integrated into decision-making processes to improve ecosystem management in different jurisdictions.